Metabolic Reprogramming—A New Era How to Prevent and Treat Graft Versus Host Disease After Allogeneic Hematopoietic Stem Cell Transplantation Has Begun - Kumari, Reena; Palaniyandi, Senthilnathan; Hildebrandt, Gerhard C. (Frontiers in Pharmacology, 2020)
Allogeneic hematopoietic stem cell transplantation (HSCT) is the only curative therapy for many types of hematological malignancies. The benefits of this procedure are challenged by graft versus host disease (GVHD), causing significant morbidity and mortality. Recent advances in the metabolomics field have revolutionized our understanding of complex human diseases, clinical diagnostics and allow to trace the de-novo biosynthesis of metabolites. There is growing evidence for metabolomics playing a role in different aspects of GVHD, and therefore metabolomic reprogramming presents a novel tool for this disease. Pre-transplant cytokine profiles and metabolic status of allogeneic transplant recipients is shown to be associated with a risk of acute GVHD. Immune reactions underlying the pathophysiology of GVHD involve increased proliferation and migration of immune cells to the target site, requiring shifts in energy supply and demand. Metabolic changes and reduced availability of oxygen result in tissue and cellular hypoxia which is extensive enough to trigger transcriptional and translational changes. T cells, major players in acute GVHD pathophysiology, show increased glucose uptake and glycolytic activity. Effector T (Teff) cells stimulated during nutrient limiting conditions in vitro or proliferating during GVHD in vivo, also increase their reliance on oxidative phosphorylation (OXPHOS) and fatty acid oxidation (FAO). Dyslipidemia, such as the increase of medium and long chain fatty and polyunsaturated acids in plasma of GVHD patients, has been observed. Sphingolipids associate with inflammatory conditions and cancer. Chronic GVHD (cGVHD) patients show reduced branched-chain amino acids (BCAAs) and increased sulfur-containing metabolites post HSCT. Microbiota-derived metabolites especially aryl hydrocarbon receptor (AhR) ligands, bile acids, plasmalogens and short chain fatty acids vary significantly and affect allogeneic immune responses during acute GVHD. Considering the multitude of possibilities, how altered metabolomics are involved in GVHD biology, multi-temporal and multivariate biomarker panels for predicting and understanding GVHD are needed. In this review, we will discuss the recent work addressing metabolomics reprogramming to control GVHD in detail.